Catatan Sebaran Baru Dromidiopsis indica Gray, 1831 (Decapoda: Brachyura: Dromiidae) dari Pantai Tengor, Lampung, Indonesia - Yudhistiro Muhammad Khalid; Achmad Farajallah; Windra Priawandputra (Jurnal Biologi dan Pembelajarannya (JB&P), 2026)
Dromidiopsis is found in the waters of Asia, Australia, Oceania, Africa, and several small islands in the Indian Ocean. In Indonesia, there are two documented reports of this genus: one in the Java Sea, where Lauridromia indica was exist, and another in the Matasiri Islands of South Kalimantan, where Dromidiopsis abrolhensis, Lauridromia indica, and Dromia intermedia were found. To provide more specific distribution records, it is important to report the discovery of Dromidiopsis indica with Gray (1831) in the waters of the Southern Peninsula of Sumatra from this study. Research conducted in October 2023 using a convenience sampling method discovered Dromidiopsis indica at Tengor Beach, Tanggamus Regency, Lampung Province, Indonesia. The distribution of the species Dromidiopssis indica is not confined to specific areas, indicating a need for further exploration and research in the Southern Peninsula of Sumatra. This report marks the first discovery of Dromidiopsis indica on the Southern Peninsula of Sumatra.